Religious Sectarianism Destroying the Peaceful Image of Islamic Country: A Case Study of Pakistan - Hamza, Muhammad; Shams, Samia (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2019)
AbstractReligious harmony considers good for the development of any sovereign country, in which different schools of thoughts/sects play a vital role in society. Some namely scholars in different religious sects of Islam such as Sunni (Wahhabi, Deobandi, Ahl-e-Hadith and Baralvi) Shia are involving in supporting of sectarianism violence and also destroying the peaceful image of the country from last three decades. Sectarianism conflict is a big hindrance for the development of religious affairs and economy of the country. This study will highlight the role of religious sects and effects on the natives of the country. How sectarianisms destroyed the peaceful image of Pakistan in the world under the shadows of Islam. This cross sectional study of Three month duration which conducted from the present and pass out students of modern educational institutions and religious Madrassa from Punjab, Khyber Pakhtunkhawa, Sindh, Baluchistan and Azad Jammu & Kashmir. For better results of the study, 400 respondents (male and female) selected and analyzed data. As per survey results and primary findings, sectarianism is a bad curse which destroyed the gross-roots of the natives of country religiously, economically and politically for last many years.AbstrakKerukunan umat beragama dianggap baik bagi perkembangan negara berdaulat, berbagai aliran pemikiran/sekte berperan penting dalam kehidupan masyarakat. Sehingga ada beberapa cendikiawan yang berbeda seperti Sunni (Wahhabi, Deobandi, Ahl-e-Hadits dan Baralvi) Syiah terlibat dalam mendukung kekerasan sektarianisme yang menghancurkan citra damai negara dari tiga dekade terakhir. Konflik sektarianisme adalah penghalang besar bagi perkembangan urusan agama dan ekonomi negara. Studi ini akan menyoroti peran sekte dan efek agama pada penduduk asli negara itu. Bagaimana sektarianisme menghancurkan citra damai Pakistan di dunia di bawah bayang-bayang Islam. Studi cross sectional ini berdurasi tiga bulan yang dilakukan dari sekarang dan lulus siswa dari lembaga pendidikan modern dan madrasah agama dari Punjab, Khyber Pakhtunkhawa, Sindh, Baluchistan dan Azad Jammu & Kashmir. Untuk hasil penelitian yang lebih baik, 400 responden (pria dan wanita) memilih dan menganalisis data. Sesuai hasil survei dan temuan utama, sektarianisme adalah kutukan buruk yang menghancurkan akar-akar kasar penduduk asli negara secara agama, ekonomi dan politik selama beberapa tahun terakhir.How to Cite: Hamza, M., Shams, S. (2019). Religious Sectarianism Destroying the Peaceful Image of Islamic Country: A Case Study of Pakistan. TARBIYA: Journal of Education in Muslim Society, 6(2), 220-232. doi:10.15408/tjems.v6i2.14961.